Child safety in day care centres within the Western Cape - Jaffer, Khadija (Department of Paediatrics and Child Health, 2018)
The aim of the study is to explore aspects of child safety in registered day care centres situated in a lower socio-economic area of the Cape Town Metropole. This can be achieved by: a) describing the physical environment in day care centres b) assessing the infrastructure of day care centres to deal with potential injurjes c) reviewing injury reporting systems already in place d) highlighting the issue of child safety in the course of conducting the study.